MINIMALLY INVASIVE SURGERY IN TREATMENT OF PATIENTS WITH METASTATIC COLORECTAL CANCER - Yu. A. Gevorkyan; V. E. Kolesnikov; N. V. Soldatkina; D. A. Kharagezov; A. V. Dashkov; D. O. Kaymakchi; E. A. Mirzoyan; S. I. Poluektov; R. E. Tolmakh; O. N. Stateshny; V. A. Doncov (Южно-Российский онкологический журнал, 2020)
Purpose of the study. Was to improve the results of treatment for metastatic colorectal cancer using laparoscopic surgical technologies.Patients and methods. We analyzed the data on 311 patients aged 44–78 years with colorectal cancer and liver metastases; in 2005–2015, all patients received treatment at National Medical Research Centre for Oncology of the Ministry of Health of Russia. The main group included 161 patients with metastatic colon cancer and resectable liver metastases receiving laparoscopic surgery; 150 patients with the same disease receiving open surgery were controls.Results. The study demonstrated that laparoscopy with a combination of developed surgical techniques significantly (р<0.05) reduced the number of surgical complications in the main group (1.8%) compared to controls (12.8%). Patients with metastatic colorectal cancer receiving laparoscopy demonstrated higher, compared to patients with standard open surgery, relative risks of cardiovascular and respiratory complications (HR=4.7, р=0.001), thrombohemorrhagic complications (HR=2.8, р=0.05) and arrhythmia (HR=3.73, р=0.07), but lower risks of surgical complications (HR=0.13, р=0.001). Survival of patients with metastatic colorectal patients was statistically significantly higher in the main group compared to controls: log‑rank test = 2.11 at р=0.035.Conclusions. Laparoscopy reduced the number of surgical complications, compared to open surgery. However, patients with comorbid pathologies showed higher relative risks of other complications.